STRATEGI MUSYRIF UNTUK MENANGGULANGI PERILAKU HOMOSEKSUAL DI TIGA PESANTREN YOGYAKARTA - M. Affan Ramadhan; Anita Aisah (Pascasarjana Universitas Al-Qolam Malang, 2025)
The rise of homosexual cases on social media within Islamic boarding schools has sparked concerns due to its moral conflict with Islamic teachings, particularly the Qur'an and As-sunnah. Therefore, preventing homosexual behavior in these environments is a critical focus for musyrif (community leaders). This research examines musyrif strategies to address homosexuality in three Islamic boarding schools in Yogyakarta, using passive participant observation, semi-structured interviews, and documentation analysis.This research concludes that the musyrif in the three boarding schools use strategies to address homosexuality, including educational steps, spiritual guidance, and technical measures such as bunk beds, CCTV, and proximity between male and female dormitories.